2020
DOI: 10.3390/ijms21249527
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Phylogeny, and Comparative Expression of the Lipoxygenase Gene Family of the Aquatic Duckweed, Spirodela polyrhiza, during Growth and in Response to Methyl Jasmonate and Salt

Abstract: Lipoxygenases (LOXs) (EC 1.13.11.12) catalyze the oxygenation of fatty acids and produce oxylipins, including the plant hormone jasmonic acid (JA) and its methyl ester, methyl jasmonate (MeJA). Little information is available about the LOX gene family in aquatic plants. We identified a novel LOX gene family comprising nine LOX genes in the aquatic plant Spirodela polyrhiza (greater duckweed). The reduced anatomy of S. polyrhiza did not lead to a reduction in LOX family genes. The 13-LOX subfamily, with seven g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Two duckweed strains (S. polyrhiza, 7498 and 7003) were grown at room temperature (22 ± 2 °C) under white light (50-80 μmol/s 2 ) as previously described (Upadhyay et al 2020a). Three growth periods (14 ± 1 day, 21 ± 1 day and 28 ± 1 day) were chosen as previously described (Mattoo et al 1992).…”
Section: Plant Material Growth Conditions Meja or Salinity Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two duckweed strains (S. polyrhiza, 7498 and 7003) were grown at room temperature (22 ± 2 °C) under white light (50-80 μmol/s 2 ) as previously described (Upadhyay et al 2020a). Three growth periods (14 ± 1 day, 21 ± 1 day and 28 ± 1 day) were chosen as previously described (Mattoo et al 1992).…”
Section: Plant Material Growth Conditions Meja or Salinity Treatmentsmentioning
confidence: 99%
“…Samples were taken at indicated timepoints, washed thrice with distilled water, frozen in liquid nitrogen and stored at − 70 °C until used. Transcript abundance of S. polyrhiza 7498 PA biosynthetic pathway genes in response to MeJA was carried out as previously described (Upadhyay et al 2020a). MeJA (Sigma, 95%) was diluted 1:10 with 95% ethanol, followed by a further dilution with sterile MilliQ water containing 0.1% Triton X-100, to a final concentration of 10 μM MeJA.…”
Section: Plant Material Growth Conditions Meja or Salinity Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to analyze new gene families with known established families during phylogenetic analyses. Therefore, to further characterize the zf_CCCH genes in soybean and its relationship with other legumes such as Medicago truncatula, Phaseolus vulgaris and Vigna unguiculata , the zf_CCCH proteins of Arabidopsis and rice were added to establish the phylogenetic relationship following the references of Rameneni, et al [ 28 ] and Upadhyay, et al [ 52 ]. The zf_CCCH protein sequences of the Medicago truncatula (50 zf_CCCHs ) , Phaseolus vulgaris (43 zf_CCCHs ) and Vigna unguiculata (49 zf_CCCHs ) were downloaded from the database of plant genomics resource Phytozome 12 using the tool of Biomart with the Pfam ID:PF00642 ( https://phytozome.jgi.doe.gov/biomart ).…”
Section: Methodsmentioning
confidence: 99%
“…Upadhyay et al [ 10 ] identified nine lipoxygenase (LOX) genes in aquatic plant, Spirodela polyrhiza . Plant LOXs catalyze hydroperoxidation at either the C-9 (9-LOX) or C-13 (13-LOX) residue of linoleic acid or linolenic acid, which are the major fatty acids in plant membrane lipid and are necessary for the biosynthesis of JA.…”
mentioning
confidence: 99%